if tanA+sinA=m and tanA-sinA=n,show that m2+n2=√mn
Answers
Answered by
7
Answer:
Step-by-step explanation:
Attachments:
![](https://hi-static.z-dn.net/files/d82/0198b4cb1fc042055a324d7c6efdafbb.jpg)
![](https://hi-static.z-dn.net/files/d84/bfa86850cfbc64f0f3402ab61da656f8.jpg)
8437704272:
hlo
Answered by
3
Answer:
Step-by-step explanation:
tanθ+sinθ=m and tanθ-sinθ=n
∴, m²-n²
=(m+n)(m-n)
=(tanθ+sinθ+tanθ-sinθ)(tanθ+sinθ-tanθ+sinθ)
=(2tanθ)(2sinθ)
=4tanθsinθ
4√mn
=4√(tanθ+sinθ)(tanθ-sinθ)
=4√(tan²θ-sin²θ)
=4√{(sin²θ/cos²θ)-sin²θ}
=4√sin²θ{(1/cos²θ)-1}
=4sinθ√{(1-cos²θ)/cos²θ}
=4sinθ√(sin²θ/cos²θ)
=4sinθ√tan²θ
=4sinθtanθ
∴, LHS=RHS (Proved)
Similar questions